Meningkatkan kecerdasan musikal anak usia dini melalui iringan alat musik gitar dan pianika - Sabhira, Sherly; Purba, Christin Natalia; Khalisah, Nur; Harianja, Sri Indriani; Muazzomi, Nyimas (Jurnal Warna : Pendidikan dan Pembelajaran Anak Usia Dini, 2025)
Musical intelligence in early childhood is the ability to understand, produce, and express music that includes rhythm, tone, harmony, and expression. This study aims to explore the role of guitar and pianica musical instruments in improving musical intelligence and fine motor development in early childhood. The method used in this study is a literature study by analyzing various sources, including scientific journals and reference books that discuss the relationship between music and child development. The results of the study indicate that the use of guitar and pianica in learning can help children understand the concept of music more deeply, improve musical memory, and strengthen hand and finger coordination, which contributes to fine motor development. In addition, musical activities carried out in groups can also improve children's social skills. Music-based learning that combines games and instruments has been shown to be more effective in fostering interest and musical skills in early childhood. In addition to the musical aspect, the use of musical instruments also has a positive impact on children's cognitive skills. Children who are accustomed to playing music tend to have better focus and concentration, and are able to recognize sound patterns more accurately. This activity also trains hand and eye coordination, which plays an important role in children's writing readiness. It is important for PAUD educators to receive adequate training in music teaching in order to optimize simple musical instrument-based learning. Thus, early music education not only impacts musical intelligence, but also children's motor, social, and cognitive skills. This study recommends the integration of music as part of the PAUD curriculum to support holistic child development.